Odpowiedzi

2009-11-05T11:50:46+01:00
A]2x³-5x²-8x+20=x²[2x-5]-4[2x-5]→[x²-4][2x-5]=[x+2][x-2][2x-5]→x₁=[-2],x₂=2, 2x=5→x₃=2,5 b]x₃-2x₂-5x+6=[x-1][x²-x-6]→Δ=b²-4ac=1+24=25 √Δ=5→x₁=1,x₂=-b-√Δ:2a=1-5:2=-2, x₃=-b+√Δ:2a=1+5:2=3 pozdrawiam
2009-11-05T13:07:48+01:00
A) 2x³-5x²-8x+20=0
2x³-8x-5x²+20=0
2x(x²-4)-5(x²-4)=0
(x²-4)(2x-5)=0
(x-2)(x+2)(2x-5)=0
x=2 ∨ x=-2 ∨ x=2½
b)x³-2x²-5x+6=0
(x-1)(x²-x-6)=0
x=1 ∨ x²-x-6=0
Δ=b²-4ac
Δ=(-1)²-4×1×(-6)
Δ=1+24
Δ=25
√Δ=5
x₁= -b -√Δ/2a
x₁= 1-5/2
x₁= -4/2
x₁= -2
x₂= -b+√Δ/2a
x₂= 1+5/2
x₂= 6/2
x₂= 3